ANALISA JARINGAN LOCAL AREA NETWORK (LAN) PADA PERUSAHAAN TERMINAL PETIKEMAS KOJA (TPK) TANJUNG PRIOK JAKARTA UTARA - Achmad Sumbaryadi; Hendro Dwi Prasetyo (Fakultas Ilmu Komputer dan Desain - Unsurya, 2017)
Corporation of TERMINAL PETIKEMAS KOJA (TPK) Tanjung Priok North Jakarta is the first private sector operator terminal in Indonesia and that is the separate excellence, so it can give an more worth and better image in public eyes and also of the competitors. This corporation give service which in the form of container loading and unloading, receiving and delivery container, behandle service, and transhipment. See from requirement of information which required shall always up to date, hence one of supplementary factor the core important is usage of network LAN. That’s why the writer in exercise of job practice doing analysis Local Area Network (LAN) at corporation of TERMINAL PETIKEMAS KOJA (TPK). Such as network peripheral analysis, application software and operating system analysis which applied at Corporation of TERMINAL PETIKEMAS KOJA ( TPK), so that can be able to know the weakness from the network configuration and can be minimalisation the problem to be repaired.